Development of financial performance of food retailers as an attribute behind the increase of food insecurity in selected Central and Eastern European Countries - Oksana Dubanych; Jan Vavřina; Josef Polák (Investment Management & Financial Innovations)
Food insecurity is not a new phenomenon even in leading European economies, but this complex problem area is facing new global challenges. This article traces the research gap in addressing food insecurity by focusing on the role of food retail chains in the former “Eastern Bloc” in light of unprecedented food price inflation and the resulting scale of demand for the services of food banks. Through empirical analysis of secondary financial corporate data, a low level of their profitability in the period of 2011–2019 was revealed, which preceded the synchronicity of two unexpected global economic downturns. Specifically, Return on Sales for food retailers located in the Czech Republic and Hungary was generally below 2%, offset by higher Total Asset Turnover figures, consistent with the need to extend the volume of goods for sale. Development in profitability in selected newer EU member states is just as significantly similar to the situation in Ukraine. The mutual interaction of factors of economic size and the country of residence of business was analyzed regarding a possible influence on their financial performance. This study concluded that the presence of unresolved market distortions can both lead to increased food insecurity and, paradoxically, contribute to increased food waste. AcknowledgmentThe authors are thankful to the Internal Grant Agency of Mendel University in Brno for financial support to carry out this research as the partial output of the project No. IGA-PEF-TP-23-015 “Zajišťování výživových potřeb obyvatelstva vzhledem k aktuálním výzvám v oblasti regenerativních přístupů při vykonávání hospodářských činností podniků agropotravinářského komplexu se zaměřením na roli tuzemských potravinových bank”.